PENERAPAN FUNGSI MANAJEMEN KELOMPOK TANI JAGUNG DI DESA LEMBEAN - Obeth ., Fakdawer; Melsje Y. Memah; Lorraine W. Th. Sondakh (AGRI-SOSIOEKONOMI, 2017)
The purposes of this research are: (1) To Identify Application of Management Function of Maize Farmer Group in Lembean Village and (2) Analyze Application of Management Function of MaizeFarmer Group In Lembean Village. This research was conducted for 5 months from February to June 2017 and located in Lembean Village, Sub-district Kauditan, North Minahasa Regenct, North Sulawesi Province. The data used in this research is Primary and Secondary data. Primary data obtained through observation in the field and directly interviews. Interviews were conducted with farmer groups related to farmer group activities to find out the description of the implementation of management functionsundertaken by farmer groups. In addition, researchers also conducted interviews with maize farmers and collectors to determine the current condition of maize prices and the flow of maize seeds from farmers tosuppliers. Secondary data is obtained from relevant literature, as well as documents and reports ownedby farmer groups and related agencies. This study focuses on the management of material flow as well asthe flow of information from the implementation of the management function of maize farmer groups inLembean. The results of the observations and interviews were analyzed by descriptive analysis method.The result of the research shows that the implementation of the management function in the maizefarming group in the sub-district of Kauditan, with management functions measured and obtained inLembean maize farmer group, Tumaratak maize farmer group and maize farming group Waleposanimplementation of management function on the implementation and evaluation well in research this is invery high category whereas for the Implementation of Management Function Planning And FunctionManagement Monitoring is on high category, on the three groups of maize farmers in Lembean village.